Middle management involvement in resource allocation - Natarajan, Siddharth; Mahmood, Ishtiaq P.; Mitchell, Will (Strategic Management Journal, 2019)
[Research Summary: Managers at multiple levels of a firm influence resource allocation but most research focuses on senior rather than middle managers. We study involvement of middle managers in decision making, focusing on how rewards and controls shape resource allocation. We argue that higher income growth uncertainty (rewards) and lower monitoring (controls) increase resource allocation most strongly when middle managers are more involved in decisions. We test the arguments for ATM and bank branch allocations in Indian banks from 2011 to 2014. We assess causal mechanisms by comparing more and less favorable conditions for allocation, as well as considering a poststudy exogenous shock. The results suggest that the rewards and controls have different associations with resource allocation depending on the involvement of senior and middle managers. Managerial Summary: The study examines how rewards and controls shape resource allocation decisions by middle managers, focusing on rewards arising from uncertainty about employee income and controls based on monitoring. The work suggests that rewards and controls that influence resource allocation by one level of managers may have less effect for another level. Hence, a firm's plans for resource deployment need to include rewards and controls that are relevant for both senior and middle managers.]